1996
DOI: 10.1111/j.1540-8191.1996.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Heparin-Bonded Circuits and Lower Anticoagulation for Coronary Artery Bypass Grafting in Jehovah's Witnesses

Abstract: Despite many advances in blood conservation techniques, a significant proportion of patients undergoing primary coronary revascularization still require homologous transfusions. Based on a large clinical experience with high-risk patients during coronary artery bypass, a comprehensive strategy to diminish perioperative blood loss was developed by integrating many individual components. An integral component in this strategy is the use of lower heparinization (activated clotting time [ACT] > 280 sec) in conjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Although not universal, 178 several studies have shown that this approach attenuates the inflammatory response to CPB as reflected by reduced complement 179 -185 and granulocyte activation. 178,180,182,183,185,[187][188][189][190][191][192][193][194][195][196][197] Some studies using reduced systemic heparin doses showed increased activation with heparin-coated circuits (as evidenced by increases in prothrombin fragment 1.2, FPA, D-dimer, and ␤ thromboglobulin values). 178,180,182,183,185,[187][188][189][190][191][192][193][194][195][196][197] Some studies using reduced systemic heparin doses showed increased activation with heparin-coated circuits (as evidenced by increases in prothrombin fragment 1.2, FPA, D-dimer, and ␤ thromboglobulin values).…”
Section: Monitoring In Patients Undergoing Procedures Involving Use Omentioning
confidence: 99%
See 1 more Smart Citation
“…Although not universal, 178 several studies have shown that this approach attenuates the inflammatory response to CPB as reflected by reduced complement 179 -185 and granulocyte activation. 178,180,182,183,185,[187][188][189][190][191][192][193][194][195][196][197] Some studies using reduced systemic heparin doses showed increased activation with heparin-coated circuits (as evidenced by increases in prothrombin fragment 1.2, FPA, D-dimer, and ␤ thromboglobulin values). 178,180,182,183,185,[187][188][189][190][191][192][193][194][195][196][197] Some studies using reduced systemic heparin doses showed increased activation with heparin-coated circuits (as evidenced by increases in prothrombin fragment 1.2, FPA, D-dimer, and ␤ thromboglobulin values).…”
Section: Monitoring In Patients Undergoing Procedures Involving Use Omentioning
confidence: 99%
“…198,199 However, findings have been inconsistent when routine doses of heparin are used, some showing lower platelet activation, 180,195 whereas others show no difference. 180,[187][188][189][190][191] However, the majority of these studies summarized in table 5, used short CPB intervals and were not powered adequately to clearly address safety of lower heparin doses with heparin-coated circuits with respect to thrombotic complications. 180,[187][188][189][190][191] However, the majority of these studies summarized in table 5, used short CPB intervals and were not powered adequately to clearly address safety of lower heparin doses with heparin-coated circuits with respect to thrombotic complications.…”
Section: Monitoring In Patients Undergoing Procedures Involving Use Omentioning
confidence: 99%
“…We collected information on the individual PBM strategies applied to manage anemia, bleeding, and coagulopathy (Table S5 to S7, Data S1). Of the 41 studies included, 26 described the application of strategies to manage anemia, 14,18,19,21,24–28,30,32–39,43–45,47,49,50,53,54 with a median of two strategies applied per study; 23 studies described the application of strategies to minimize bleeding, 14,17–20,24–30,33,37,38,40,43,44,47–49,52,54 with a median of two strategies per study; 15 studies described applying strategies for coagulopathy, 14,18,22,26,30,33,36–38,43,44,48,49,52,54 with a median of one strategy per study (Table S18, Data S1).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the last decade, multiple studies have documented the risks of allogeneic transfusion [1][2][3][4][5][6] and others have explored the use of bloodless alternatives [1,4,[7][8][9][10]. Consensus statements have been published [11][12][13][14], interdisciplinary conferences have been organized [11,[15][16][17][18][19], and bloodless medicine and surgery centers have been developed throughout the country [14].…”
Section: -~0mentioning
confidence: 99%